1980
DOI: 10.1038/ki.1980.164
|View full text |Cite
|
Sign up to set email alerts
|

Leukopenia, hypoxia, and complement function with different hemodialysis membranes

Abstract: Complement activation during exposure of plasma to cuprophan has been postulated to cause leukopenia and hypoxia in hemodialysis patients. To determine if hypoxia is related to leukopenia and if complement activation leads to a depletion of functional complement components, we dialyzed four patients three times sequentially against each of four types of membranes: cuprophan, regenerated cellulose, cellulose acetate, and polyacrilonitrile. Within 20 min there was a marked leukopenia with cuprophan from 5541 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(51 citation statements)
references
References 10 publications
1
49
1
Order By: Relevance
“…Hypoxemia during hemodialysis has been recognized since the early days of dialysis (26)(27)(28)(29)(30)(31)(32). Over the years, several mechanistic explanations have been put forward.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia during hemodialysis has been recognized since the early days of dialysis (26)(27)(28)(29)(30)(31)(32). Over the years, several mechanistic explanations have been put forward.…”
Section: Discussionmentioning
confidence: 99%
“…Jacob et al have found a similar degree of hypoxemia during dialysis with cuprophone, regenerated cellulose, cellulose acetate, and polyachrylonitrile membranes (25). However, the effects of these membranes on the leukocyte count were markedly different, with cuprophane producing the most and polyachrylonitrile the least changes.…”
Section: Role Of the Dialyzer Membranementioning
confidence: 89%
“…Evi dence in support of this view can be summarized as fol lows: (1) whereas peripheral neutropenia peaks in the first 30 min of dialysis and resolves usually by the end of 1 h, hypoxemia persists for the duration of dialysis [1][2][3]; (2) peripheral neutropenia does not occur or is minimal when dialysis is performed with polyacrylonitryl or polysulfon membranes or with reused cellophane mem branes, yet hypoxemia does develop [2,3], and (3) when cellophane membranes are used to perform isolated ul trafiltration (i.e., in the absence of dialysate), peripheral neutropenia but not hypoxemia is observed [2,4], It should be mentioned, however, that a recent report [5] appears to reopen the question. In this study, patients were dialyzed using either cuprophane or polyacrylonitryl membranes, while the dialysis bath contained either bi carbonate (with CO2 bubbling) or acetate (without CO2 bubbling).…”
Section: Complement and Leukocyte-mediated Pulmonary Dysfunctionmentioning
confidence: 99%